Factors Influencing the Choice of Non-Long-Term Contraception Methods in Women of Reproductive Age - Ni Wayan Rusminiati; Ni Wayan Suarniti; Gusti Ayu Eka Utarini (Sean Institute, 2025)
Family planning services are one way to reduce the Maternal Mortality Rate (MMR) by regulating the time, distance, number of pregnancies, so as to minimize the possibility of pregnant women experiencing complications that endanger their lives or the fetus. In Mengening Village, 58.2% use Non-MKJP. The purpose of this study was to determine the factors underlying the choice of Non-MKJP in WUS at the Mengening Village Community Health Center, Kubutambahan II Health Center working area in 2025. This type of research uses a quantitative descriptive approach (cross-sectional). Implementation in April - May 2025. The sample consisted of 118 WUS who visited the Mengening Village Community Health Center. Data collection was done by distributing questionnaires. Data analysis used a frequency distribution. The results of the study showed the identification of factors underlying the use of Non-MKJP contraceptives in WUS, namely age 20-35 years (61.9%), the latest secondary education (89.8%), knowledge about Non-MKJP in the sufficient category (50.8%), decisions taken together (83.1%), married status (100%). Women of childbearing age are expected to understand the contraceptives they are currently using and those they plan to use. Healthcare workers are expected to continue providing routine education about long-term contraceptive methods (MKJP) to women of childbearing age, and future researchers are expected to examine the effects of non-MKJP contraceptive use on women of childbearing age.